PERENCANAAN PENGGUNAAN ENERGI TERBARUKAN SOLAR PANEL UNTUK RUMAH TINGGAL - Muhammad Naim; Aziz Asmauna; Harjuma; M Yasir Pohan (Jurnal Genta Mulia, 2026)
In the development of Indonesia, both the past mass and the energy front mass will continue to makechanges and developments. This is due to developments and innovations in the use of renewable energy.Likewise with PLTS, which has developed quite a message and also continues to experience fairly rapiddevelopment, not only industry but also PLTS can be developed for home-scale or small-scale energyusers. This is because the use of PLTS is quite efficient, both in terms of construction costs andmaintenance costs.